The Comparison of High Flow Nasal Cannula Oxygen and Conventional Oxygen Therapy on Early Effect Hemodynamic Indicators in Post – Upper Abdominal Surgery Patients: A Pilot Study - Luki Sumaratih; Rudyanto Soedono; Dita Aditianingsih (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Background The effect of high-flow nasal cannula (HFNC) on hemodynamic data of the patients is still unknown. This was a pilot study to evaluate the effect of HFNC and conventional oxygen therapy (COT) on post-upper abdominal surgery. Methods This was an open-label randomized controlled trial (RCT) at tertiary hospital between February-June 2019. Inclusion criteria were ASA III, aged 18-65 years, BMI 18,5-29 kg/m2. Exclusion criteria were patients with unstable hemodynamic with vasopressors, general oedema, and uncooperative. Thirty patients were recruited and divided into HFNC group (n=15) and COT group (n=15). Hemodynamic parameters were recorded using the bedside monitor (heart rate, respiratory rate, and mean arterial pressure) as well as the electrical cardiometry using ICON® measurements (stroke volume index, cardiac index and systemic vascular resistance index); laboratory parameters were ScVO2 and lactate serum. Data were collected at 0, 30 and 60 minutes post-extubation. Results The General Linear Model (GLM) tests on clinical parameters (HR, RR and MAP) were P= 0.20; P=0.72; P = 0.18, ICON® parameters (SVI, CI and SVRI) were P= 0.02;P =0.64; P =0.64 meanwhile ScVO2 and lactate were P = 0.35 and P = 0.22. Despite those results, at some period of measurements there were a tendency of a better outcomes of most parameters for the HFNC group. Conclusion According to the results, the only statistically significant outcome was SVI (P =0.02) after the analysis between those two groups. However, the HFNC group showed a clinically improvement of the other outcomes among post-upper abdominal surgery patients. Keywords High flow nasal cannula, conventional oxygen therapy, haemodynamic, abdominal surgery